2010
DOI: 10.1111/j.1442-200x.2009.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe hand foot and mouth disease

Abstract: It is not clear why attending child care centers was associated with HFMD severity. Further study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 5 publications
1
24
0
1
Order By: Relevance
“…Belonging to the picornaviridae family, this virus, associated with Enterovirus 71 (EV71), is responsible for nearly all of the HFMD epidemics in Southeast Asia [13,14]. In Japan, CA16 was reported to be a prevalent type, while EV71 recurrent every 3 years [10,15]. In Singapore, from 2001 to 2008, the predominant EV strains isolated from HFMD cases were CA16 and EV71 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Belonging to the picornaviridae family, this virus, associated with Enterovirus 71 (EV71), is responsible for nearly all of the HFMD epidemics in Southeast Asia [13,14]. In Japan, CA16 was reported to be a prevalent type, while EV71 recurrent every 3 years [10,15]. In Singapore, from 2001 to 2008, the predominant EV strains isolated from HFMD cases were CA16 and EV71 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have identified possible predictors associated with increased probability of severity, such as children who attend child care centres 25 , has leukocytosis 17 , has limb weakness 26 , or has persistent fever 27 , there is still much uncertainty about the relative importance of these predictors. Limited studies have systematically evaluated the criteria for early screening of severe cases and some studies have only categorized severe and mild HFMD based on the length of hospitalization rather than a clinical measure of severity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have systematically evaluated the criteria for early screening of severe cases and some studies have only categorized severe and mild HFMD based on the length of hospitalization rather than a clinical measure of severity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…EV71 and coxsackievirus A16 (CA16) have been identified as the two major etiological agents of hand, foot and mouth disease (HFMD) [8,9]. Large outbreaks of HFMD have recently been reported in the Asia-Pacific region, which is becoming a common acute viral disease in these areas and posing a serious health threat to children [10-13].…”
Section: Introductionmentioning
confidence: 99%